PENGARUH ORGANIZATIONAL JUSTICE TERHADAP ORGANIZATIONAL COMMITMENT YANG DIMEDIASI OLEH JOB SATISFACTION PADA KARYAWAN PT SEABREEZ INDONESIA - Warsindah, Lucy; Silvicana, Yola (Manajemen Bisnis Kompetensi, 2016)
ABSTRACTThis study aimed to analyze the influence of Organizational Justice on Organizational ComÃÂmitment mediated by Job Satisfaction at PT Seabreez Indonesia. The sampling method is used census by distributing questionnaires to all permanent employees in PT Seabreez InÃÂdonesia totaling 150 employees. Data analysis method used is to use descriptive statistical analysis and Structural Equation Modeling (SEM). Based on the results of hypothesis testÃÂing, it can be concluded that the Organizational Justice on Organizational Commitment has a ÃÂ² of 0.474 with a p-value 0.015 < 0.05, which means that H1 Organizational Justice supÃÂported a positive effect on Organizational Commitment. While the test results as a mediator of Job Satisfaction on Organizational Commitment to Organizational Justice has a value of ÃÂ² of 0.496 with a p-value of 0.000 < 0.05, the H2 is also supported, which means may mediate the effect of Job Satisfaction on Organizational Justice to Organizational CommitÃÂment. It can be concluded that the mediation of a test that shows a direct comparison of the effect of the ÃÂ² value of 0.474 while the indirect effect to the ÃÂ² value of 0.496, which means a greater influence on Organizational Justice to Organizational Commitment, Job Satisfaction through instead of Organizational Justice on Organizational Commitment.Keywords: organizational justice, job satisfaction, organizational commitment